The influence of the geographical features of Kyrgyzstan on the choice of types of recreational activities (A case study: issyk-kul region) - Choduraev TM; Toktoraliev ET (Annals of Environmental Science and Toxicology - Peertechz Publications, 2023)
Economic impact is a stimulating effect on the economic condition of various regions. The paper describes the influence of the structure of the object on the choice of recreational activities, taking into account the sensitivity of the mountain structure to anthropogenic impact. Determined the value of the initial values of the applications of sociological research, which used to calculate the natural-territorial complexes - these are water bodies located on the territory with identified orographic structures, surrounded by forests, taking into account possible options for recreation. Evaluated of the assessment and comfort of the recreational area, based on the identification of psychophysiological characteristics, such as the sensation of noise, thermal effects of the environment. The development of recreation centers associated with the demand for recreationists, which also determined by the level of development and material base. Studies on the study of the Issyk-Kul region that the geographical characteristics of the territory (relief, water bodies, climate, etc.) have not only attractiveness, but inhibitory factors for rare types of recreational activities.